Punching up or punching down? How stereotyping the rich and the poor impacts redistributive preferences in Germany - Matthias Diermeier; Madeleine L. Fischer; Judith Niehues (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
Redistribution and the welfare state have been linked by academic discourse to narratives that portray specific societal groups as 'deserving' or 'undeserving'. The present analysis contributes to this scholarship in a twofold manner. First, it provides a holistic view on the beneficiaries and benefactors of welfare and asks how the public perception of the rich and the poor drives redistributive preferences. It is revealed that these beliefs, particularly about the 'deserving' poor, are significant determinants of strong redistributive preferences. Despite powerful prevailing prejudices about the rich, support for redistribution in Germany is not motivated by the urge to castigate this group for their affluence. Second, we are interested in the distribution of the different moralistic beliefs about the rich and the poor over socio-demographic characteristics. Regarding stereotypical beliefs about the poor, we quantify the phenomenon of 'punching down', performed by those immediately above the lowest income quintile. In fact, members of the second income quintile show levels of disdain similar to their wealthier counterparts on the other end of the income distribution. On the other hand, moralistic beliefs about the 'deserving poor' are equally held across different socio-economic levels. Implications and limitations of our findings are also discussed.
Keywords: D63; D64; I32; I38; C38; 330; Inequality; welfare state; redistribution; poor; rich; distancing